AB0382 Assessing neuropathic pain components in patients with rheumatoid arthritis. (23rd January 2014) - Detert, J.; Höhne-Zimmer, V.; Schönberger, S.; Roehner, E.; Burmester, G.-R.; Buttgereit, F.
Abstract : Background: This is a prospective analysis of a sample frequency of neuropathic pain (NP) components in patients (pts) with rheumatoid arthritis (RA). The current drug regimen addresses only inadequately NP phenomena and other factors such as anxiety, depression, and coping behavior. Objectives: RA-pts have a NP component in addition to the inflammatory pain due to joint destruction and the resulting nerve irritation. Methods: In this investigation 204 pts (163 ♀, 41 ♂) with RA were included according to classification criteria of ACR 1987. The disease duration of pts was ≥12 months. The mean age was 58.8 (SD: 13.5). All pts provided demographic information, and answered questions on their disease course (e.g. start of disease, medication). Furthermore, multiple data on pain perception (e.g. temporal occurrence, quality, quantity, characteristics) were collected. NP was also identified specifically using the pain DETECT Questionnaire (PDQ) in an interview.A descriptive statistical analysis was performed with SPSS 19. Results: All data were collected in our outpatient department from June 2008 to November 2010. The mean disease activity score (DAS28ESR ) was 3.2. The following table shows a selection of key results for the characterization of pain in RA-patients. Conclusions: Most pts reported typical nociceptive pain. In their own words, pts also described an inflammatory pain and selected the characteristics of this pain from a list. Pain attacks occur more frequently in fall and winter. More than a third of patients report pain attacks that occur throughout the day. Hence, pain therapy should be adjusted accordingly. Disclosure of Interest: J. Detert Grant/Research support from: Pfizer GmbH & Co, V. Höhne-Zimmer: None Declared, S. Schönberger: None Declared, E. Roehner: None Declared, G.-R. Burmester Grant/Research support from: Pfizer GmbH & Co, Consultant for: Pfizer GmbH & Co, Speakers Bureau: Pfizer GmbH & Co, F. Buttgereit Grant/Research support from: Pfizer GmbH & Co, Consultant for: Pfizer GmbH & Co, Speakers Bureau: Pfizer GmbH & Co